Sudden expansion of a single brown bear maternal lineage across northern continental Eurasia after the last ice age: a general demographic model for mammals? - M. Korsten; S. Y. W. Ho; Malgorzata Pilot; Y. Mertzanis; A. Giannakopoulos; A. A. Vorobiev; N. I. Markov; A. P. Saveljev; E. A. Lyapunova; A. V. Abramov; P. Mannil; H. Valdmann; et al. (2013)
The brown bear has proved a useful model for studying Late Quaternary mammalian phylogeography. However, information is lacking from northern continental Eurasia, which constitutes a large part of the species' current distribution. We analysed mitochondrial DNA sequences (totalling 1943 bp) from 205 bears from northeast Europe and Russia in order to characterize the maternal phylogeography of bears in this region. We also estimated the formation times of the sampled brown bear lineages and those of its extinct relative, the cave bear. Four closely related haplogroups belonging to a single mitochondrial subclade were identified in northern continental Eurasia. Several haplotypes were found throughout the whole study area, while one haplogroup was restricted to Kamchatka. The haplotype network, estimated divergence times and various statistical tests indicated that bears in northern continental Eurasia recently underwent a sudden expansion, preceded by a severe bottleneck. This brown bear population was therefore most likely founded by a small number of bears that were restricted to a single refuge area during the last glacial maximum. This pattern has been described previously for other mammal species and as such may represent one general model for the phylogeography of Eurasian mammals. Bayesian divergence time estimates are presented for different brown and cave bear clades. Moreover, our results demonstrate the extent of substitution rate variation occurring throughout the phylogenetic tree, highlighting the need for appropriate calibration when estimating divergence times. Â© 2009 Blackwell Publishing Ltd.